Lumbar V3 interneurons provide direct excitatory synaptic input onto thoracic sympathetic preganglionic neurons, linking locomotor, and autonomic spinal systems - Chacon, Camila; Nwachukwu, Chioma V.; Shahsavani, Narjes; Cowley, Kristine C.; Chopek, Jeremy W. (Frontiers in Neural Circuits, 2023)
Although sympathetic autonomic systems are activated in parallel with locomotion, the neural mechanisms mediating this coordination are incompletely understood. Sympathetic preganglionic neurons (SPNs), primarily located in the intermediate laminae of thoracic and upper lumbar segments (T1-L2), increase activation of tissues and organs that provide homeostatic and metabolic support during movement and exercise. Recent evidence suggests integration between locomotor and autonomic nuclei occurs within the brainstem, initiating both descending locomotor and sympathetic activation commands. However, both locomotor and sympathetic autonomic spinal systems can be activated independent of supraspinal input, in part due to a distributed network involving propriospinal neurons. Whether an intraspinal mechanism exists to coordinate activation of these systems is unknown. We hypothesized that ascending spinal neurons located in the lumbar region provide synaptic input to thoracic SPNs. Here, we demonstrate that synaptic contacts from locomotor-related V3 interneurons (INs) are present in all thoracic laminae. Injection of an anterograde tracer into lumbar segments demonstrated that 8-20% of glutamatergic input onto SPNs originated from lumbar V3 INs and displayed a somatotopographical organization of synaptic input. Whole cell patch clamp recording in SPNs demonstrated prolonged depolarizations or action potentials in response to optical activation of either lumbar V3 INs in spinal cord preparations or in response to optical activation of V3 terminals in thoracic slice preparations. This work demonstrates a direct intraspinal connection between lumbar locomotor and thoracic sympathetic networks and suggests communication between motor and autonomic systems may be a general function of the spinal cord. Deleted: It is becoming increasing clear that Deleted: function Deleted: in Deleted: particular sympathetic function increases in parallel as one begins to locomote.